Comparison of Efficacy of Localized Narrow-Band UVB Therapy Versus Localized PUVA Therapy in Chronic Hand Eczema - Khadka, Dhan Keshar; Agrawal, Sudha; Rijal, Arpana; Shrestha, Samir (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Hand eczema is a type of dermatitis largely confined to the hands. Narrowband UVB (NBUVB) appears to be as effective as topical PUVA therapy in the treatment of chronic hand dermatitis. However, the risks of phototoxicity and dyspigmentation associated with local PUVA therapy make NBUVB therapy a preferable initial therapeutic option. Methods and Methodology: A total of 40 patients with chronic hand eczema were randomly divided into two groups: Group A (20) receiving localized NBUVB and Group B (20) receiving localized PUVA therapy. They were administered the designated treatment modality for the period of 8 weeks. They were evaluated every 2 weeks to see for the clinical response and any side effects. Results: In group A, there was around 47% and 85% improvement in Clinical Assessment Score (CAS) at weeks 4 and 8 respectively. Similarly, in group B, there was around 52% and 86% improvement in CAS at weeks 4 and 8 respectively. The improvement in terms of the mean of CAS in cases of group B was more compared to group A. (p=0.636 at week 4 and 0.578 at week 8). Conclusion: Light-based modalities of treatment in the form of localized NBUVB and PUVA can be considered as an alternative treatment of choice in cases of hand eczema as they have been shown effective by the reduction in the clinical assessment score. However, there was no statistically significant difference in the reduction in the mean clinical assessment score among the patients treated with either localized NBUVB or PUVA.